2018
DOI: 10.22214/ijraset.2018.5234
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Revolution of Flat Plate Collector for Solar Water Heater

Abstract: Energy is the significant need of the world either for nutrition or for development of the society. The power bank of the earth is the sun, which has tremendous amount of energy in it and will never exhaust. The conversion of solar energy to thermal energy is the function of collector. Flat plate collector (FPC) are cost effective and more convenience in all collectors. The paper reveals the different design of the flat collectors used to enhance the efficiency of the collector. Effect of using phase change ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Solar water heating has been extensively studied and it has been reported that it can supply about 70% of sanitary water heating demand on residential and commercial facilities (Bracamonte et al, 2015). Solar water heaters play a vital role in low temperature applications especially in domestic area (Patil, 2015). Flat Plate Solar Collector is one of the known devices developed for harnessing solar energy and converting it to heat, particularly for applications requiring energy delivery at moderate temperature of up to 100 o C (Sukhatme and Nayak, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Solar water heating has been extensively studied and it has been reported that it can supply about 70% of sanitary water heating demand on residential and commercial facilities (Bracamonte et al, 2015). Solar water heaters play a vital role in low temperature applications especially in domestic area (Patil, 2015). Flat Plate Solar Collector is one of the known devices developed for harnessing solar energy and converting it to heat, particularly for applications requiring energy delivery at moderate temperature of up to 100 o C (Sukhatme and Nayak, 2008).…”
Section: Introductionmentioning
confidence: 99%